2016
DOI: 10.2139/ssrn.2729348
|View full text |Cite
|
Sign up to set email alerts
|

Is Gender Diversity Profitable? Evidence from a Global Survey

Abstract: Analysis of a global survey of 21,980 firms from 91 countries suggests that the presence of women in corporate leadership positions may improve firm performance. This correlation could reflect either the payoff to nondiscrimination or the fact that women increase a firm's skill diversity. Women's presence in corporate leadership is positively correlated with firm characteristics such as size as well as national characteristics such as girls' math scores, the absence of discriminatory attitudes toward female ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0
10

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(107 citation statements)
references
References 18 publications
2
95
0
10
Order By: Relevance
“…And those companies with a larger percentage of women in upper management may also have a financial advantage. In their study of the business case for increasing female leadership in corporate settings, Noland et al (2016) found no real effect on firm performance merely from the presence of a female CEO. However, there was a demonstrable advantage to firm performance when there were a significant number of women executives, which "underscores the importance of creating a pipeline of female managers and not simply getting women to the very top" (p. 16).…”
Section: Women Ceosmentioning
confidence: 95%
See 3 more Smart Citations
“…And those companies with a larger percentage of women in upper management may also have a financial advantage. In their study of the business case for increasing female leadership in corporate settings, Noland et al (2016) found no real effect on firm performance merely from the presence of a female CEO. However, there was a demonstrable advantage to firm performance when there were a significant number of women executives, which "underscores the importance of creating a pipeline of female managers and not simply getting women to the very top" (p. 16).…”
Section: Women Ceosmentioning
confidence: 95%
“…An examination of some of the largest companies in the US (in Fortune 500 and 1000 companies), the UK (FTSE 100), and Canada (Financial Post 500) demonstrates this pattern at less than 5 percent (Adler, 2015). A broader study that represented almost 22 000 publicly traded corporations in 91 countries also found fewer than 5 percent of firms had women CEOs (Noland et al, 2016). Another research group has published numbers indicating a range of 9-12 percent of worldwide companies which have a woman CEO (or equivalent top position title) (Grant Thornton, 2014Thornton, , 2015.…”
Section: Women Ceosmentioning
confidence: 99%
See 2 more Smart Citations
“…First, our findings help to reconcile the mixed evidence obtained to date. Generally, the results on the impact of gender diversity on firm performance run the gamut, from those that find a positive impact on performance (Gul et al, 2011;Campbell and Minguez-Vera, 2008;Noland et al, 2016;Kang et al, 2009;Schmid and Urban, 2016) to those that find a negative impact (Ahern and Dittmar, 2012;Adams and Ferreira, 2009), to those that find little or no impact (Farrell and Hersch, 2004;Ferrari et al, 2016). While some previous papers documented evidence of non-linearities regarding some performance measures (de Andres and Vallelado, 2008), our study is first in providing comprehensive evidence that the impact of board gender diversity on performance depends on how much diversity the board has already achieved and on how well-managed the institution is overall.…”
Section: Introductionmentioning
confidence: 99%